2021
DOI: 10.1080/02827581.2021.1883729
|View full text |Cite
|
Sign up to set email alerts
|

Keeping mixtures of Norway spruce and birch in production forests: insights from survey data

Abstract: Admixtures of birch in Norway spruce plantations are being promoted as a means to increase habitat and species diversity. The implications of this mixture were analysed with regional survey data from southern Sweden. Permanent sample plots from the Swedish National Forest Inventory (NFI), with Norway spruce and admixture of birch, were used to describe the temporal trends in the admixture, regarding species composition and competitive strength. Observations from thinned plots show a higher harvest removal in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…A previous study on the climatic variations of the three aspect-slopes indicated that the southwest slope was warmer than the mountaintop [13,43]. Tree growth is influenced by different factors, including neighborhood competitors [28,[44][45][46] and climate [44,47,48]. However, by using the same region, block size and shape, number of species, planting pattern (random), density and age, we tried to eliminate any possible source of variation other than those being investigated, i.e., aspectslope and species.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the climatic variations of the three aspect-slopes indicated that the southwest slope was warmer than the mountaintop [13,43]. Tree growth is influenced by different factors, including neighborhood competitors [28,[44][45][46] and climate [44,47,48]. However, by using the same region, block size and shape, number of species, planting pattern (random), density and age, we tried to eliminate any possible source of variation other than those being investigated, i.e., aspectslope and species.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, birch is known to be very sensitive to snow and ice mechanical damage, especially in sparse forest stands that might be its disadvantage at some exposed sites [15]. Anyway, admixture of birch in Norway spruce plantations was pointed, especially in the newest works [44,45] as an efficient means to increase habitat and species diversity, including diversity of ground flora [46], invertebrates [47] or birds [48].…”
Section: Ecological Aspectsmentioning
confidence: 99%
“…Birch is known to establish abundantly after disturbances like fire (Ascoli and Bovio 2010;Dzwonko et al 2015), storms (Ilisson et al 2007;Vodde et al 2010) or clearfellings (Holgén and Hånell 2000;Götmark et al 2005;Karlsson and Nilsson 2005). Birch in the boreal forest is important for several ecosystem services, in example provisioning wood for pulp, timber and bioenergy (Rytter 2004;Woxblom and Nylinder 2010;Felton et al 2021;Lidman et al 2021) or as fodder for ungulate foraging (Cederlund et al 1980;Hörnberg 2001). In Sweden, it is common to find birch growing in mixtures with other species, particularly Norway spruce (Picea abies H.…”
Section: Introductionmentioning
confidence: 99%